New sanctions of the European Union and United States against Russia and their impact on Tajikistan’s socio-economic development - A. Kh. Rakhmonov (Управление)
The article examines the socio-economic relationship between Tajikistan and Russia, the new European Union and USA sanctions against Russia and their impact on the economy and well-being of Tajikistan, and the role of Society for Worldwide Interbank Financial Telecommunication (SWIFT) in Russian and Tajik banks, including the disconnection of SWIFT from Russian banks and its impact on remittances of migrant workers in Tajikistan. Attention is paid to Tajikistan’s crisis management policy. After gaining independence, Tajikistan’s economy suffered greatly from the civil war in the republic. Russia is one of the main donors to Tajikistan’s economy. There are countries that are more connected to Russia than Tajikistan, but it is difficult to find a country that could compete with Tajikistan in terms of dependence on Russia. Almost all sectors of Tajikistan’s economy depend on Russia: Tajikistan is a donor country for migrant workers, and remittances from migrant workers play an important role in Tajikistan’s economy. Only, at the expense of money transfers of Tajik labor migrants, the banking sector of Tajikistan is supported. Over the years of independence, Tajikistan has not taken its economy out of the influence of Russia. The dependence of the Tajik economy on Russia manifested itself in the very first days of the conflict actions on the territory of Ukraine in February 2022. After the statement of Western countries on the introduction of new sanctions to restrict the access of some Russian banks to the SWIFT, the problems of the financial intermediation market of Tajikistan were exposed. An unprecedented package of sanctions by Western countries due to the situation with Ukraine has already led to a number of problems inside Tajikistan. European Union and USA sanctions against Russia have also had a strong impact on all sectors of Tajikistan’s economy, from food prices to the banking sector. The aim of the article is to assess the role of the new European Union and USA sanctions against Russia in connection with the conflict in Ukraine and their impact on the economy and welfare of Tajikistan.